Pengaruh Variabel Makro Inflasi, Kurs, Suku Bunga, dan PDB terhadap Indeks Harga Saham Gabungan: Penelitian - RD. Chandra Gunawindharto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine the effect of inflation, exchange value, interest rate, and gross domestic product against the Indonesia Composite Index (ICI). The type of research used explanatory research, with quantitative approach and took all time series data covering inflation, exchange value, interest rate, and gross domestic product and Indonesia Composite Index (ICI) for the period of 2000 until 2024. The data analysis used multiple linear regression analysis using SPSS 26. The results of this study indicate that the value of coefficient of determination(R2) 84.9% which means independent variables affect the dependent variable 84.9% and the rest is 15.1% influenced by other variables outside this study. F test results indicate that the independent variables of inflation, exchange value, interest rate, and gross domestic product simultaneously have significant effect on the Indonesia Composite Index (ICI). The result of t test shows that the inflation variable partially positively influenced the Indonesia Composite Index(ICI), exchange rate variable partially have significant positive effect on Indonesia Composite Index, interest rate variable partially have significant negative effect on Indonesia Composite Index(ICI), , while GDP partially have positif effect on Indonesia Composite Index(ICI).